The imprint of humans on landscape patterns and vegetation functioning in the dry subtropics - Baldi, Germán; Verón, Santiago R.; Jobbágy, Esteban G. (Global change biology, 2013)
Dry subtropical regions (DST), originally hosting woodlands and savannas, are subject to contrasting human pressures and land uses and different degrees of water limitation. We quantified how this variable context influences landscape pattern and vegetation functioning, by exploring the associations between three groups of variables describing (i) human pressures (population density, poverty, and market isolation) and climate (water availability), (ii) landscape pattern (woody cover, infrastructure, paddock size, etc.), and (iii) vegetation functioning (magnitude and stability of primary productivity), in regions of Asia, Africa, Australia, and America. We collected data from global socioeconomic databases and remote sensing products for 4525 samples (representing uncultivated and cultivated conditions), located along 35 transects spanning semiarid to subhumid conditions. A Reciprocal Averaging ordination of uncultivated samples revealed a dominant gradient of declining woody cover accompanied by lower and less stable productivity. This gradient, likely capturing increasing vegetation degradation, had a negative relationship with poverty (characterized by infant mortality) and with market isolation (measured by travel time to large cities). With partial overlaps, regions displayed an increasing degradation ranking from Africa to South America, to Australia, to North America, and to Asia. A similar analysis of cultivated samples, showed a dominant gradient of increasing paddock size accompanied by decreasing primary productivity stability, which included all regions except Asia. This gradient was negatively associated with poverty and population density. A unique combination of small paddocks and high infrastructure differentiated Asian cultivated samples. While water availability gradients were related to productivity trends, they were unrelated to landscape pattern. Our comparative approach suggests that, in DST, human pressures have an overwhelming role driving landscape patterns and one shared with water availability shaping vegetation functioning.